2018
DOI: 10.1007/s10658-018-1596-3
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium oxysporum colonizes the stem of resistant tomato plants, the extent varying with the R-gene present

Abstract: Fusarium oxysporum colonizes the stem of resistant tomato plants, the extent varying with the R-gene present van der Does, H.C.; Constantin, M.E.; Houterman, P.M.; Takken, F.L.W.; Cornelissen, B.J.C.; Haring, M.A.; van den Burg, H.A.; Rep, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…A similar difference was reported for other systems, like the interaction between tomato and Fo47 or Forl. Two weeks post-inoculation Fo47 biomass was 10-fold less than that of the pathogen (Validov et al, 2011). These observations imply that in early stages of the interaction Fo endophytes are less efficient root colonizers than pathogens.…”
Section: Host Colonizationmentioning
confidence: 80%
See 2 more Smart Citations
“…A similar difference was reported for other systems, like the interaction between tomato and Fo47 or Forl. Two weeks post-inoculation Fo47 biomass was 10-fold less than that of the pathogen (Validov et al, 2011). These observations imply that in early stages of the interaction Fo endophytes are less efficient root colonizers than pathogens.…”
Section: Host Colonizationmentioning
confidence: 80%
“…Horizontal transfer of a pathogenicity chromosome from Fol to Fo47 turned the endophyte into a tomato pathogen (Ma et al, 2010). Subsequent studies revealed that chromosome transfer from a cucurbit-infecting Fo strain could transform Fo47 into a cucurbit pathogen (van Dam et al, 2017). Vice versa, loss of a dispensable pathogenicity chromosome from a Fol strain resulted in loss of pathogenicity (Vlaardingerbroek et al, 2016).…”
Section: F Oxysporum Endophytism and Pathogenicity Are Genetically Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolations were conducted at various times during July 2018-September 2019 and a total of up to 350 symptomatic plants (as stock plants, rooted cuttings, vegetative plants or flowering plants) of 10 strains (genotypes) were included depending on what was in production (Table 1). Plants were propagated either in coco fibre (coco coir) substrate from various suppliers or in rockwool blocks (Grodan) and were provided with the appropriate nutrient regimes and lighting conditions as required for commercial hydroponic production (Small 2017). The environmental conditions during the periods over which isolations were conducted varied according to the production facility, with temperatures in the range of 24-32°C and relative humidity in the range of 50% to 85%.…”
Section: Isolations From Plantsmentioning
confidence: 99%
“…Bioassays were performed either on the tomato (Solanum lycopersicum) line C32 or Money Maker, susceptible to Fusarium wilt, or on the wild tomato relatives S. pimpinellifolium (accession LA1578) and S. chmielewskii (accessions LA1840, LA2663 and LA2695) in a climate-controlled greenhouse with a day-night temperature of 25 • C, 16 h light/ 8 h dark, and a relative humidity of 65%. Fol029 (race 3, sFP2381, carrying phleomycin resistance [18]) and Fo47 (sFP1544, carrying hygromycin resistance, [19]) were inoculated on the aforementioned tomato lines. Bioassays using various Fusarium species were performed on the tomato line C32 using the wild-type pathogen Fol4287 (sFP801) [20], and endophyte Fo47 (sFP730) [10], F. hostae (sFP2236), F. proliferatum (sFP2240), F. redolens (sFP4856) [21], and F. solani (sFP895).…”
Section: Plant Lines and Fungal Strainsmentioning
confidence: 99%